Analysis of Russian Federation Foreign Policy in the Field of International Information Security - Zinovieva, E. S. (Vestnik MGIMO-Universiteta, 2014)
Information and communication technologies (ICT) play an essential role in the improvement of the quality of life, economic and socio-political of individual countries and humanity in general. However, ICT development is fraught with new challenges and threats to international and national security. Interstate rivalry in the information sphere generates conflicts, an extreme form of which is an information war. Since 1998, the Russian initiative supports the international cooperation on information security at the global and regional level as well as within the framework of the bilateral relations. The article analyzes the characteristics of the global information society, which has a decisive influence on the international security in the information age, as well as international cooperation in this field. The analysis of Russian foreign policy initiatives in the field of international information security is also presented. Today more than 130 countries develop cyber capabilities, both defensive and offensive, that pose serious threats to the international stability. It's difficult to trace the source of information attacks and its consequences can be devastating and cause retaliation, including the use of conventional weapons. In this situation Russian approach, advocating for the development of the rules of conduct of States and demilitarization of information space in order to ensure its safety, seems urgent and relevant with the international situation.